Restructuring retirement risks - Blitzstein, David (Oxford University Press, 2006)
David Blitzstein is the Director of the United Food and Commercial Workers International Union (UFCW) Negotiated Benefits Department where he advises local unions in collective bargaining on pension and health insurance issues and consults with the Union's 150 jointly trusted health and welfare and pension plans nationwide. Mr. Blitzstein also serves as trustee of the UFCW Industry Pension Fund, and the UFCW National Health and Welfare Fund. Mr. Blitzstein represents the UFCW as a member of the working committee of the National Coordinating Committee for Multiemployer Plans. In addition he serves on the Pension Research Council Advisory Board at the Wharton School; he is a member of the Employee Benefits Research Institute and the National Academy of Social Insurance. He received the BS degree from the University of Pennsylvania and he received the MS in Labor Studies from the University of Massachusetts in Amherst